2.2 eV luminescence in GaN - Hofmann, D. M.
The yellow Luminescence in GaN centered at 2.2 eV has been studied in various epitaxial layers grown by MOVPE on sapphire and by the sandwich sublimation method on 6H-SiC substrates. The photoluminescence and optically detected magnetic resonance results can be consistently explained by a recombination model involving shallow donors and deep donors.